A Review in the Jurisprudential Ruling of Condition of Absence of Marriage Portion in Marriage - Hamid Masjedsaraie; Sayyid Rasool Mousavi (آموزه‌‌های فقه مدني)
Although the determination of dower (marriage portion, marriage settlement) in a permanent marriage contract is not a condition based on verse 24 of Surah An-Nisa (in Arabic text: النساء‎), traditions reported by numerous authorities (successive widely transmitted) and the consensus of jurists and marriage without mentioning the marriage portion is also a completely valid contract, but it is assumed sometimes that not only the dower is not mentioned in the text of the contract, but marriage is conditioned to absence of marriage portion and the lack of marriage portion is conditioned by one of the spouses or both. Now the question is: What is basically, the ruling of the condition of absence of marriage portion in marriage, and consequently, what is its effect on the validity and invalidity of the marriage contract itself? The present article, using descriptive-analytical method, has tried to achieve the conclusion that the condition of absence of marriage portion in marriage is correct or, at least, can be used as a presumption, despite the famous jurisprudential opinion that such a condition is invalid, while criticizing and rejecting the evidence of the ruling, such as verses and ḥadīth (pl. aḥādīth, literally “talk” or “discourse”, narrations), in addition to weakening the famous opinion and this is the main finding of the research.